Front Cover: A Dithiol Compound Binds to the Zinc Finger Protein TRAF6 and Suppresses Its Ubiquitination (ChemMedChem 23/2017). (7th December 2017) - Koga, Ryoko; Radwan, Mohamed O.; Ejima, Tomohiko; Kanemaru, Yosuke; Tateishi, Hiroshi; Ali, Taha F. S.; Ciftci, Halil Ibrahim; Shibata, Yuri; Taguchi, Yuu; Inoue, Jun‐ichiro; Otsuka, Masami; Fujita, Mikako
Abstract : The Front Cover shows that a dithiol compound namedSN‐1 binds to TRAF6 protein and suppresses its auto‐ubiquitination and downstream NF‐κB activation to express proteins related to cancer and inflammation. The TRAF6 has five zinc fingers C‐terminal to the N‐terminal RING finger domain with two zincs.SN‐1 is considered to bind directly to a zinc of the first zinc finger, disrupting ubiquitin ligase activity of the neighboring RING finger. This study shows a platform for new small molecules targeting zinc finger proteins, coming after the conventional drugs targeting zinc enzymes. Cover illustration by Hiroe Kamasaki, Soft Sync Inc. More information can be found in the Full Paper by Masami Otsuka, Mikako Fujita et al. onpage 1935 in Issue 23, 2017 (DOI:10.1002/cmdc.201700399 ).